Mid-Flexion, Anteroposterior Stability of Total Knee Replacement Implanted with Kinematic Alignment: A Randomized, Quantitative Radiographic Laxity Study with Posterior-Stabilized and Medial-Stabilized Implants - Scott, David F; Hellie, Amy A (Journal of bone and joint surgery. American volume, 2023)
This article was updated on January 4, 2023, because of a previous error, which was discovered after the preliminary version of the article was posted online. On page 16, in Figure 5, the x-axis that had read "P<0.0086" now reads "KSS Pain (p=0.02)," and the value for the MS group that had read "48.9" now reads "48.8."This article was updated on January 6, 2022, because of a previous error. On page 13, in the section entitled "Results," the sentence that had read "However, when only the subset of female subjects was considered, the MS group demonstrated significantly less anteroposterior laxity in 90° of flexion than the MS group (2.3 versus 5.4 mm; p = 0.008)." now reads "However, when only the subset of female subjects was considered, the MS group demonstrated significantly less anteroposterior laxity in 90° of flexion than the PS group (2.3 versus 5.4 mm; p = 0.008)." Stability in mid-flexion is important for satisfactory clinical outcomes following total knee arthroplasty (TKA). The purpose of the present study was to compare the anteroposterior stability of knees that had been treated with a posterior-stabilized (PS) device or a medial-stabilized (MS) device. We hypothesized that mid-flexion laxity would be greater in the PS group and that clinical outcome scores would be better for the group with lower laxity. Sixty-three patients who had been randomly selected from a larger randomized, prospective, blinded clinical trial underwent primary TKA with either a PS implant (n = 30) or an MS implant (n = 33). Range of motion, the Knee Society Score (KSS), and the Forgotten Joint Score (FJS) were collected, and anteroposterior laxity with the knee in 45° and 90° of flexion was evaluated with stress radiographs. In 45° of flexion, the MS group demonstrated significantly less total anteroposterior displacement than the PS group (mean, 3.6 versus 16.5 mm; p ≤ 0.0001). In 90° of flexion, the total anteroposterior displacement was not significantly different for the 2 groups when both male and female patients were included (mean, 3.9 versus 5.9; p = 0.07). However, when only the subset of female subjects was considered, the MS group demonstrated significantly less anteroposterior laxity in 90° of flexion than the PS group (2.3 versus 5.4 mm; p = 0.008). The groups did not differ significantly in terms of preoperative age, body mass index, sex distribution, FJS, KSS, or range of motion, and they also did not differ in terms of postoperative FJS or range of motion. However, all 33 patients in the MS group returned to sports as indicated in question 12 of the FJS, compared with 19 subjects in the PS group (p = 0.0001). The postoperative KSS Pain, Pain/Motion, and Function scores were all significantly higher in the MS group than the PS; specifically, the mean KSS Pain score was 48.8 in the MS group, compared with 44.8 in the PS group (p = 0.02); the mean KSS Pain/Motion score was 98.4 in the MS group, compared with 89.5 in the PS group (p < 0.0001); and the mean KSS Function score was 95.5 in the MS group, compared with 85.7 in the PS group (p = 0.003). Mid-flexion laxity was greater in patients with PS implants than in those with MS implants, and laxity in 90° was greater in the subset of female patients in the PS group. The decreased laxity observed in the MS group correlated with higher KSS Pain, Pain/Motion, and Function scores as well as with a higher rate of return to sports activities. Therapeutic Level I . See Instructions for Authors for a complete description of levels of evidence.